Influence of Damage on Variations of Material Thermal Properties - Madej, J. (Engineering Transactions, 2003)
The aim of this paper is presentation of an attempt of identification of the changes of thermal properties of the material in correlation with changes of its structure during the damage process. The review of the most frequently used methods of damage detection in constructional materials has been enclosed. In comparison to these approaches, a new method is presented – namely the method of assessment of the level/stage of damage based upon changes/fluctuations of heat transmission property of the material, which occur in the damage cumulation regions. In the considerations, the continuum mechanics of damage was assumed. The assumption is supported by numerical calculations, which are in full agreement with experimental investigations made by means of thermos-vision techniques. Experiments performed and suitable numerical simulation confirms the essential connection between the state of damage and thermal transmission properties of the investigated materials.